2021
DOI: 10.3390/microorganisms9122501
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Transovarial Transmission of Bartonella henselae in Rhipicephalus sanguineus sensu lato Ticks Using Artificial Feeding

Abstract: Bartonella henselae is a slow-growing, Gram-negative bacterium that causes cat scratch disease in humans. A transstadial transmission of the bacteria from larvae to nymphs of Rhipicephalus sanguineus sensu lato (s.l.) ticks, suspected to be a potential vector of the bacteria, has been previously demonstrated. The present study aims to investigate transovarial transmission of B. henselae from R. sanguineus s.l. adults to their instars. Adult ticks (25 males and 25 females) were fed through an artificial feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…While C. felis fleas are the primary vectors of B. henselae among cats (Chomel et al, 1996), previous studies have shown the potential role of ticks as vectors for this Bartonella species (Cotté et al, 2008;Wechtaisong et al, 2020Wechtaisong et al, , 2021 (Kang et al, 2016). These findings underscore the need for a comprehensive understanding of potential vectors and their role in the epidemiology of Bartonella species among ruminants.…”
Section: Discussionmentioning
confidence: 95%
“…While C. felis fleas are the primary vectors of B. henselae among cats (Chomel et al, 1996), previous studies have shown the potential role of ticks as vectors for this Bartonella species (Cotté et al, 2008;Wechtaisong et al, 2020Wechtaisong et al, , 2021 (Kang et al, 2016). These findings underscore the need for a comprehensive understanding of potential vectors and their role in the epidemiology of Bartonella species among ruminants.…”
Section: Discussionmentioning
confidence: 95%
“…to replicate within multiple tick species cell lines (Billeter et al, 2009), the ability of Bartonella-infected ticks to transmit Bartonella infection between animal models while feeding (Noguchi, 1926;Reis et al, 2011), and the detection of Bartonella spp. DNA or bacilli in infected tick midgut, salivary glands, and feces (Cotté et al, 2008;Reis et al, 2011;Wechtaisong et al, 2021). Despite these findings, there is still a lack of consensus regarding the ability of ticks to vector Bartonella species.…”
Section: Discussionmentioning
confidence: 99%
“…The transovarial and transstadial transmission of B. henselae , B. grahamii , and B. schoenbuchensis have been recently demonstrated [ 56 ], while the transmission of B. birtlesii to susceptible mice, using laboratory-infected I. ricinus , was previously achieved [ 57 ]. Rhipicephalus sanguineus being the most prevalent tick in companion animals, has recently been used in similar studies [ 58 , 59 ] but evidence that this tick species can be the vector of Bartonella sp. is also still missing.…”
Section: Discussionmentioning
confidence: 99%